UPAYA PENGOLAHAN LIMBAH JAGUNG MELALUI INOVASI PEMBUATAN BRIKET TONGKOL JAGUNG SEBAGAI ENERGI ALTERNATIF DI DESA SAMBALIA - Armansyah, Ismayadi; Fetrosia, Riska; Pratama, Sugi Artha; Astuti, Luviana; Hartati, Sri; Ningrat, Lalu Fayadh Rusya; Syahfitri, Dian Aulia; Bianti, Baiq Asri; Pebrina, Tria Rizki; Wiryajati, I Ketut (Jurnal Wicara, 2025)
Sambalia Village is one of 11 villages located in Sambelia Subdistrict in the northern part of East Lombok Regency. Sambalia Village has great potential in the agricultural sector, especially in corn production, which is abundant. However, this abundant corn production also has a negative impact on the lack of utilization and processing of post-harvest waste from this commodity. The 2025 PMD Community Service Program in Sambalia Village was implemented to support the village's potential while making a tangible contribution to the community. The implementation method used a participatory approach through socialization and training on work programs involving village officials, community leaders, and the people of Sambalia Village. The main program focused on community empowerment through socialization and training on making corn cob briquettes as an alternative energy source and strengthening business capacity through socialization on product packaging and business licensing. The results showed that the community was quite enthusiastic about participating in the program, participants were able to practice new skills, and there was an awareness of the importance of alternative fuel innovation. The main obstacles encountered included limited time, equipment, and the sustainability of post-KKN assistance. Thus, the KKN PMD activity in Sambalia Village provided a learning experience for students and tangible benefits for the community in opening up new economic opportunities.